Similar sounding words writing strategy by learners of Mandarin as a foreign language - Ang, Lay Hoon; Abdul Halim, Hazlina (Faculty of Language and Communication, Universiti Malaysia Sarawak, 2019)
A general feature observed in foreign language classroom is the usage of communication strategies by the learners in their attempts to manipulate a limited linguistics system to communicate. This research aims to investigate the usage of similar sounding words as a written communication strategy in learning Mandarin. The respondents were 59 second- and third-year Malaysian students learning Mandarin as a foreign language at a public university. An open-ended questionnaire was set to gauge respondents’ perception on the strategies used, and was divided into four parts, namely the demographic data and 3 parts of written tasks. The respondents were required to write a dialogue, answer questions on their hobbies and construct sentences using the words given. A total of 77 data of similar sounding words were found. The results showed that similar sounding words strategy was mostly applied to retroflex, alveolar, affricate, fricative, plosive, aspirated and unaspirated sounds. Another one third of the data consisted of syllables which were formed based on the learners’ understanding of the pronunciation. It was found that the strategy provides constructive help in getting the message across despite the inaccurate pronunciation. The findings also mirror the constructive learning attitude and aggressive struggle put in by the learners, and therefore, a positive strategy that should be encouraged.